PERAN MEDIA SOSIAL DINAS PARIWISATA KABUPATEN LOMBOK TENGAH MELALUI INSTAGRAM @GOMANDALIKA DALAM PROMOSI PARIWISATA - Paramita, Eka Putri; Dewi, Juliana Ayu Puspita (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
This study aims to analyze the role of the Instagram social media account @gomandalika, managed by the Tourism Office of Central Lombok Regency, in promoting tourism. The method used is qualitative with a descriptive approach. Data were collected through in-depth interviews, as well as observation and documentation analysis. The theoretical framework used is the Marketing Communication Theory, specifically the AISAS model (Attention, Interest, Search, Action, Share). The results indicate that the @gomandalika Instagram account plays a significant role as an effective strategic tool for tourism promotion in Central Lombok. The result indicate found that the account successfully attracts attention and interest through engaging visual content, drives users to seek more information and take action by visiting tourist destinations, and encourages sharing of experiences, thereby expanding the reach of promotion. The findings highlight the importance of high-quality visual content, relevant information, and interactive features in influencing tourist decisions and building a positive image for Central Lombok tourism. This study recommends enhancing content quality and interaction to further optimize the account's role in tourism promotion. Keywords: Social Media Role, Instagram, Tourism Promotion, Central Lombok, AISAS Model.